IMPROVING OUTPATIENT ANTIBIOTIC PRESCRIBING FOR COMMON PEDIATRIC RESPIRATORY INFECTIONS (Multidisciplinary Journal of Science and Technology, 2026)
Inappropriate antibiotic prescribing for common pediatric respiratory infections remains a major driver of antimicrobial resistance, avoidable adverse drug events, and unnecessary healthcare costs. Most respiratory illnesses in children seen in outpatient settings are viral or self-limited, yet antibiotics are still frequently prescribed because of diagnostic uncertainty, time pressure, caregiver expectations, and inconsistent adherence to clinical pathways. This article presents a practical, clinic-ready approach to improving outpatient antibiotic prescribing for children with respiratory infections. It emphasizes three linked pillars: improving diagnostic accuracy using evidence-based criteria and targeted testing, optimizing antibiotic selection and duration when treatment is indicated, and embedding stewardship into routine workflow through decision support, communication strategies, and audit-feedback cycles.